2006
DOI: 10.1021/ac060053k
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multibed Sorption Trap, Comprehensive Two-Dimensional Gas Chromatography, and Time-of-Flight Mass Spectrometry System for the Analysis of Volatile Organic Compounds in Human Breath

Abstract: A method for the determination of volatile organic compounds (VOCs) at sub-trace levels in breath samples based on a multibed sorption trap for the collection and concentration of VOCs, a comprehensive multidimensional gas chromatograph (GCxGC) for the separation of complex mixtures, and a time-of-flight mass spectrometer detector is designed and developed. The good performance of the trap tube device developed for the concentration together with the high sensitivity and separation power of the GCxGC results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 38 publications
5
90
0
1
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 12 Similar trap configurations to the one used in this study have previously been described using four-bed [17,20] and three-bed configurations [14]. The use of a three-bed trap is adequate for the analysis of breath samples and a previous study has managed to detect more than 250 VOCs using this configuration [14].…”
Section: Page 12 Of 32mentioning
confidence: 88%
See 4 more Smart Citations
“…A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 12 Similar trap configurations to the one used in this study have previously been described using four-bed [17,20] and three-bed configurations [14]. The use of a three-bed trap is adequate for the analysis of breath samples and a previous study has managed to detect more than 250 VOCs using this configuration [14].…”
Section: Page 12 Of 32mentioning
confidence: 88%
“…As there is no single sorbent material that meets the full ideal criteria for concentrating all VOCs from an air matrix, a multi-bed trap must be used for this purpose [17,18]. In this study, we used a three-bed trap for general breath monitoring as it has been found to be effective in analyzing common VOCs present in breath samples [14]. Quantities of 2.5±0.2 mg of Carboxen 1000 and Carbopack X A vacuum pump (Air Cadet Vacuum Station, Barnant Co., Barrington, IL, USA) was used to pull sample gas from left to right through the trap tube shown in Figure 1 at a sample flow rate of 31 cm 3 ·min -1 .…”
Section: Apparatusmentioning
confidence: 99%
See 3 more Smart Citations